Submarine landslide-induced tsunami model using nonlinear shallow water equations in (b, s) coordinate and extended boussinesq equations - Pham, Van Khoi; Lee, Changhoon; Vu, Van Nghi (Journal of Transportation Science and Technology, 2022)
Due to earthquakes or other earth phenomena, a landslide occurs underwater and thus tsunami is generated and propagates without much energy loss even at long distances. After the tsunami arrives at the coastline, it may cause serious casualties. The submarine landslide and the tsunami should be analyzed together to predict the inter-connected phenomena. In this study, we simulate submarine landslide using the one-dimensional conservative form of the nonlinear shallow water equations (NSWE) in (b,s) coordinate [1]. Where and are the elevations of debris bottom and surface, respectively. The NSWE is discretized using the finite volume method employing the Harten-Lax-van Leer (HLL) approximate Riemann solver and the total variation diminishing (TVD) limiter to deal with numerical discontinuities. To simulate landslide-induced tsunami, we use the one-dimensional form of the extended Boussinesq equations considering time-varying debris surfaces [2] which extends Madsen and Sorensen's extended Boussinesq equations [3]. An Adams-Bashforth-Moulton predictor-corrector scheme is used to discretize the extended Boussinesq equations in time. The submarine landslide and the induced tsunami are simulated in some test cases.
Keywords: Submarine landslide; tsunami; nonlinear shallow water equations; extended Boussinesq equations; numerical simulation